Comparison of Visual Simple Reaction Time Performances of Boxers and Wrestlers - Dinçer, Nevzat; Kilinç, Zühal; Ilbak, Ismail (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It is known that reaction time, which is of great importance in terms of athlete performance, is one of the most difficult sports performance parameters to develop. Reaction time performance in Athletes may vary according to the sport branch in terms of development. Especially in combat sports such as boxing and wrestling, reaction time is of such great importance that it can directly or indirectly affect the outcome of the competition. Aim: In this study, it was aimed to compare the visual simple reaction time performances of boxing and wrestling athletes. By comparing the simple visual reaction times of boxers and wrestlers, the effects of both branch trainings on the reaction time were tried to be determined. Methods: This research was carried out with the participation of 30 male athletes between the ages of 14-17. It was held with the participation of a total of 30 male athletes, including 15 boxers and 15 wrestlers, who have been licensed contestants for at least three years and are still actively participating in the competitions. The heights of the participants were measured with a wall-mounted stadiometer (Holtain Ltd. England), their body weights were measured with an electronic scale (Seca, Germany), and their visual simple reaction time performance was measured with a Reaction Time device (Hubbard Scientific 6027). Data were analyzed with the IBM Statistics (SPSS, ver. 22.0, Armonk, NY) program. Results: The mean age of the boxing group (N=15) was 15.46±1.06, the mean height was 175.53±4.18, the mean body weight was 61.00±8.03 and the mean reaction time was 23.66±2.99. The mean age of the wrestling group (N=15) was 15.40±1.12, the mean height was 170.46±4.29, the mean body weight was 62.80±8.65 and the mean reaction time was 25.93±2.68. Conclusion: In this study comparing the visual simple reaction time performances of boxers and wrestlers, it was concluded that boxing training is more effective in shortening reaction time performance compared to wrestling training.